2023
DOI: 10.3390/v15020583
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Analysis of Influenza A(H3N2) and B/Victoria Viruses Detected in Myanmar during the COVID-19 Pandemic in 2021

Abstract: An influenza circulation was observed in Myanmar between October and November in 2021. Patients with symptoms of influenza-like illness were screened using rapid diagnostic test (RDT) kits, and 147/414 (35.5%) upper respiratory tract specimens presented positive results. All RDT-positive samples were screened by a commercial multiplex real-time polymerase chain reaction (RT-PCR) assay, and 30 samples positive for influenza A(H3N2) or B underwent further typing/subtyping for cycle threshold (Ct) value determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, from 2019 to 2022, the evolution of the Yunnan strains showed relatively stability with a high nucleotide sequence homology, predominantly clustering in the 3C.2a1b.1b clade for 2019–2021 and the 3C.2a1b.2a.1a.1 clade for 2022. This pattern diverges markedly from Myanmar circulating strains in 2019 (3C.2a1b) and 2021 (3C.2a1b.2a.2a.3) and Italy/Australia circulating strains in 2021 and 2022 (3C.2a1b.2a.2) [ 16 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 75%
“…However, from 2019 to 2022, the evolution of the Yunnan strains showed relatively stability with a high nucleotide sequence homology, predominantly clustering in the 3C.2a1b.1b clade for 2019–2021 and the 3C.2a1b.2a.1a.1 clade for 2022. This pattern diverges markedly from Myanmar circulating strains in 2019 (3C.2a1b) and 2021 (3C.2a1b.2a.2a.3) and Italy/Australia circulating strains in 2021 and 2022 (3C.2a1b.2a.2) [ 16 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 75%
“…Of the remaining 587 articles, 547 were discarded for not matching the inclusion criteria (of these, 62 were not further considered since no reported influenza cases were type B), 7 for being based on the WHO FluNet and/or GISAID database, 3 for being previous reports from the GIHSN, and 4 because of overlap with more recent and/or larger articles based on the same data sources. A total of 26 articles were included in the systematic review: their main characteristics are reported in Table 1 [ Soldevila 2022, Murillo-Zamora 2021, Korsun 2021, Panatto 2021, Pablo-Marcos 2020, Miron 2021, Hu 2021, Omer 2022, Olson 2022, Auvinen 2022, Kuzmanovska 2021, Wagatsuma 2022, Heinzinger 2021, Rios-Silva 2022, Suntronwong 2021, da Costa 2022, Melidou 2020, Huang 2022, O’Neill 2022, Kolosova 2022, Peck 2023, Chon 2023, Merced-Morales 2022, Melidou 2022, Sominina 2022, Song 2022 ]. Europe was the most represented area (12 articles, of which 2 reported findings from multiple countries in the WHO European Region), followed by Asia (n=6), North America (n=5), and Oceania and South America (n=1 each).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the immune response to contemporary FLUBV lineages, B/Washington/02/2019 (B/WA) was selected to represent the B/Vic lineage and B/Oklahoma/10/2018 (B/OK) was selected to represent the B/Yam lineage. B/Washington/02/2019 was included in the 2020-2021 quadrivalent influenza vaccine and belongs to the recently emerged subclade, V1A.3, of the Victoria lineage (34). B/Oklahoma/10/2018 (Clade 3A), which is antigenically similar to the B/Yam isolate in the 2020-2021 quadrivalent vaccine, was circulating in the U.S. just prior to the onset of the COVID-19 pandemic.…”
Section: Contemporary Flubvs Elicit Asymmetric Cross-protection Again...mentioning
confidence: 99%